24‐2: Development of Methods to Reduce Blue Light Hazard from Displays. Issue 1 (28th June 2022) - Harris, Derek; Garbar, Arkady; Broyles, Paul J.; Mitzel, Kelly; Binger, Benjamin; Batdorf, Elishaa
Abstract : New materials have been developed for LED backlit displays to reduce the hazard associated from shorter wavelength blue light. This can be done without sacrificing luminance or color gamut.